Inequalities in Regional Film Exhibition: Policy, Place and Audiences. Issue 2 (April 2021) - Merrington, Peter; Hanchard, Matthew; Wessels, Bridgette
Abstract : This article questions the variety of film exhibition in four English regions. While a regional and national frame is the focus of cultural policy in relation to film audience development in the UK, our analysis examines relational, localised and sub-regional film cultures in order to understand how differing levels of film exhibition influence people's sense of place. This is framed within a discussion of cultural inequality more generally. In the UK, questions of engagement with different types of film exhibition have gained greater prominence recently, but there has been limited attention paid to how audiences understand their geographic relationship with film exhibition. Drawing on 200 semi-structured, qualitative interviews with a wide range of film viewers across four English regions, the North East, North West, South West and Yorkshire and the Humber, we assess perceptions of film exhibition in these regions. In doing so, we characterise five different modes of place in relation to the breadth of film exhibition, from distinctive film cities to mainstream multiplex towns. In particular, we focus on how access to film is simultaneously narrated through both localised proximity to cinemas of different types and virtual access to film through online platforms. This work provides further evidence of the uneven provision of diverse film in England but shows how film audiences relationally interpret their engagement within film as a cultural form.